2006
DOI: 10.1088/0031-9155/51/9/001
|View full text |Cite
|
Sign up to set email alerts
|

Depth of interaction resolution measurements for a high resolution PET detector using position sensitive avalanche photodiodes

Abstract: We explore dual-ended read out of LSO arrays with two position sensitive avalanche photodiodes (PSAPDs) as a high resolution, high efficiency depth-encoding detector for PET applications. Flood histograms, energy resolution and depth of interaction (DOI) resolution were measured for unpolished LSO arrays with individual crystal sizes of 1.0, 1.3 and 1.5 mm, and for a polished LSO array with 1.3 mm pixels. The thickness of the crystal arrays was 20 mm. Good flood histograms were obtained for all four arrays, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
141
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 139 publications
(146 citation statements)
references
References 30 publications
3
141
1
1
Order By: Relevance
“…A stable temperature is preferred for these dual-ended readout detector modules. Although our results showed that the PSAPDs work well at room temperature (32), the temperature of the detector box becomes much higher than room temperature when several PSAPDs, preamplifiers, and other electronics parts are enclosed. To ensure low and stable temperature, the detector boxes were cooled, and the temperature variation of the detector boxes was controlled to be less than 61°C during imaging.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…A stable temperature is preferred for these dual-ended readout detector modules. Although our results showed that the PSAPDs work well at room temperature (32), the temperature of the detector box becomes much higher than room temperature when several PSAPDs, preamplifiers, and other electronics parts are enclosed. To ensure low and stable temperature, the detector boxes were cooled, and the temperature variation of the detector boxes was controlled to be less than 61°C during imaging.…”
Section: Discussionmentioning
confidence: 59%
“…As shown previously (32), light loss along the crystal length is essential for high-resolution DOI measurement with dual-ended readout. In this work, unpolished LSO arrays were used to provide a strong depth dependence in the scintillation light reaching the 2 ends of the array.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…4. 20 The electronically collimated beam width at the phosphor-coated crystal was estimated to be 2-3 mm. All PMTs were biased at −1400 V. Detector signals were digitized at 5 GS/s using a DRS-based digitizer and each digitized pulse spanned 200 ns.…”
Section: C1 Single Crystalsmentioning
confidence: 99%